Text and Emotion Analysis of Twitter Data - Anand, Neetu; Kumar, Tapas (International Journal of Computer Sciences and Engineering, 2025)
The intensification of Technology has altered the means of people’s communication by means of opinions, views, sentiments and emotions regarding particular product, services, and people on social networking sites .Social Networking sites are defined as a network of reaction, interaction and relations. Many Social Networking sites, like facebook, whatsapp, Twitter, LinkedIn, Google+, YouTube, Pinterest, Instagram, and Tumblr are the medium to convey the user emotions in form of comments for particular topic. But day by day as huge amount of data is generated from these sites. It becomes a challenging task to perform such type of analysis on big data. R is used to perform the analysis of tweets data that are having a size in GBs. Sentiment analysis, subjectivity analysis and opinion mining are the various techniques to process the review .This paper presented an approach to analyze and visualize twitter data with R. Mainly four types of attitudes are connected with each text positive, negative, neutral and uninterested. Each tweet is analyzed for detecting the sentiments attached to it.